Meningkatkan Kualitas Pendidikan di Indonesia: Peran Sentral Pilar-Pilar Pendidikan dalam Membentuk Generasi Unggul - Mhd. Zidan Firmansyah; Septria Sa'duh; Restu Permohonan Hasibuan; Gusmaneli Gusmaneli (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2023)
This article analyses the efforts made to improve the quality of education in Indonesia, with a special emphasis on the important role of education pillars in the formation of a superior generation. Education in Indonesia faces many problems, such as inequality, limited access and variations in education quality. This article aims to explain the role of the key pillars of education, namely curriculum, teaching staff, infrastructure and community engagement. The curriculum is considered the foundation that shapes the way students think and have skills. The article discusses the importance of curriculum review to ensure relevance to local and global requirements and to utilise technology as an enabler for effective learning. The second pillar discusses the role of teachers as an important factor in disseminating knowledge and values to students. Considered important strategies to produce high-quality educators are qualification upgrading, continuous training and pedagogical skills development. Talking about education infrastructure means providing adequate physical and technological facilities. Talking about the sustainability and accessibility of infrastructure and the use of technology to support distance learning. The fourth pillar emphasises that community participation is crucial to building an enabling educational environment. In this article, we will discuss the roles played by parents, local communities and the private sector in supporting and complementing government efforts to improve the quality of education. This article provides a complete overview of how these pillars of education can shape a superior generation in Indonesia by detailing their benefits. It is hoped that the implementation of integrated strategic actions in each pillar will be a strong foundation for achieving the long-term goal of improving the quality of education in Indonesia.